Linguistic methods for investigating concepts in use - M.M. Kurbanova; G.B. Ataeva (Research Parks Publishing LLC, 2020)
The article examines the linguistic research methods used in modern linguistics. New approaches and techniques are proposed: inverse methods, matrix approaches.